Landscape context matters for attractiveness and effective use of road underpasses by bats. (September 2019) - Laforge, Alexis; Archaux, Frédéric; Bas, Yves; Gouix, Nicolas; Calatayud, François; Latge, Thomas; Barbaro, Luc
Abstract: The worldwide expansion of road networks is a major concern in biological conservation because of its predominantly negative effects on terrestrial fauna. Roads also affect bats, acting as barriers to movements and causing direct mortality by collisions with vehicles. Among wildlife crossing structures existing to maintain landscape connectivity, road underpasses are considered as one of the most effective conservation measure for bats. While a few studies assessed the effects of underpass attributes on bat use, none to date has assessed the impact of landscape context on underpass use and attractiveness. To address this knowledge gap, we monitored bat activity during three consecutive nights around 24 underpasses selected along a gradient of forest cover. We compared bat activity below and above underpasses (i.e., underpass use), at road sections with and without underpasses and at habitats adjacent to roads (i.e., underpass attractiveness). We found a significant positive effect of forest cover on both underpass use and attractiveness for Myotis spp. and Barbastella barbastellus, and significant negative effects of distance to the nearest forest patch for Rhinolophus spp. and hedgerow length for Myotis spp. Our study highlights the key influence of landscape context on road underpass efficiency to maintain landscape connectivity for bats. We advocate for incorporating a landscape-scale approach in the decision-making process of underpass location during road project planning to enhance efficiency of such costly crossing structures. Highlights: Landscape context is a key factor of road underpass efficiency for bats. Forest cover improves underpass use and attractiveness for mouse-eared and barbastelle bats. Hedgerow length and distance to forest patch decrease underpass efficiency for mouse-eared and horseshoe bats, respectively. It is critical to incorporate a landscape-scale approach for underpass location strategy during road project planning.